2022
DOI: 10.32674/jcihe.v14i1.3027
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Self-perceived Employability and Its Determinants Among International Students in the United States

Abstract: The outcome of international education attracts increasing interests among scholars in the perceived employability and education-to-work transition. Yet, there is a lack of empirical studies focusing on understanding international students’ perceived employability and the strategies to improve their employability. The purpose of this study is to explore the perceived employability and its factors (e.g. demographic factors, educational factors, work-related factors, language and U.S. experience factors, and fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Different studies have tried to confirm the model fit of the original SPE scale with one factor loading in a variety of contexts, including studies from Iran, Australia, USA, Italy, Taiwan, South Africa and Poland (Cheung et al, 2018;di Fabio, 2014;Engelberg and Limbach-Reich, 2012;Maiolo et al, 2013;Praskova et al, 2015;R€ aty et al, 2018;Udayar et al, 2018;Villarreal, 2017). They have also satisfactorily tested the SPE scale with two-factor loadings on internal and external employability (Dra zi c et al, 2018;Goodman and Tredway, 2016;Huang, 2015;Kasler et al, 2017;Niu et al, 2022;Vargas et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have tried to confirm the model fit of the original SPE scale with one factor loading in a variety of contexts, including studies from Iran, Australia, USA, Italy, Taiwan, South Africa and Poland (Cheung et al, 2018;di Fabio, 2014;Engelberg and Limbach-Reich, 2012;Maiolo et al, 2013;Praskova et al, 2015;R€ aty et al, 2018;Udayar et al, 2018;Villarreal, 2017). They have also satisfactorily tested the SPE scale with two-factor loadings on internal and external employability (Dra zi c et al, 2018;Goodman and Tredway, 2016;Huang, 2015;Kasler et al, 2017;Niu et al, 2022;Vargas et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…, 2018; Goodman and Tredway, 2016; Huang, 2015; Kasler et al. , 2017; Niu et al. , 2022; Vargas et al.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Rothwell et al (2008) defined SPE as an individual's perceived ability to achieve sustainable employment in line with their professional qualifications, or their perception or belief about how easy it will be to find a new job. Students with a high level of SPE are typically able to create strategies for dealing with real-world situations (Niu et al, 2022), such as the complex situation of the COVID-19 pandemic. Improving students' SPE during the pandemic required individuals to self-manage their own careers and take responsibility for their own employability by relying on key factors such as proactivity, adaptability and entrepreneurial thinking and behavior (Capone et al, 2021).…”
Section: Self-perceived Employabilitymentioning
confidence: 99%
“…Desrochers and Dahir (2000) and Sicherman and Galor (1990) stressed that career ambitions favorably affect individuals' future goals. Niu et al (2022) investigated students' self-perceived employability, ambition, and university commitment in human resource development (HRD) programs in the United States. Their findings revealed that self-perceived employability was positively correlated with ambition and university commitment.…”
Section: Career Ambitionmentioning
confidence: 99%